Mechanical properties and macro–micro failure mechanisms of granite under thermal treatment and inclination - Yue Cao; Xiaowu Zhang; Lei Sun; Yadong Zheng; Chong Li (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract The coupling effects of inclination angle (θ) and high temperature (T) on rock degradation present significant construction challenges for underground engineering projects, such as underground coal gasification, inclined mining pillars, and nuclear waste repositories. This study is built on a novel combined compression and shear test system, investigating granite’s physical and mechanical properties and macroscopic failure characteristics under varying temperatures and inclination angles. Additionally, acoustic emission technology was used to analyze the impact of inclination and temperature on the micro-failure behavior of the specimens. The experimental results indicate that as the inclination angle increases, the specimens’ peak compressive strength and elastic modulus decrease linearly. In contrast, the shear stress increases non-linearly, suggesting that additional shear stress accelerates the initiation and propagation of cracks. Furthermore, these mechanical parameters initially increase with rising temperatures before decreasing, with a temperature threshold identified at 400 °C. The effect of inclination angle on the failure mode of the specimens is more pronounced than that of temperature; as the inclination angle increases, the failure mode transitions from splitting failure to shear failure at any given temperature. Acoustic emission results reveal that the specimens’ microcrack initiation (CI) and damage (CD) thresholds reduce with increasing inclination, while the corresponding shear stress increases. As temperature rises, the CI and CD thresholds exhibit an initial increase attended by a decrease. Finally, founded on the experimental findings, a multivariate equation was established to accurately predict the peak compressive strength and elastic modulus about θ and T. The results of this study provide valuable insights and references for the construction of underground thermal engineering under complex conditions.